2007
DOI: 10.1098/rstb.2007.2110
|View full text |Cite
|
Sign up to set email alerts
|

Thermal substitution and aerobic efficiency: measuring and predicting effects of heat balance on endotherm diving energetics

Abstract: For diving endotherms, modelling costs of locomotion as a function of prey dispersion requires estimates of the costs of diving to different depths. One approach is to estimate the physical costs of locomotion (P mech ) with biomechanical models and to convert those estimates to chemical energy needs by an aerobic efficiency (hZP mech /Vo 2 ) based on oxygen consumption (Vo 2 ) in captive animals. Variations in h with temperature depend partly on thermal substitution, whereby heat from the inefficiency of exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 172 publications
(196 reference statements)
0
41
0
Order By: Relevance
“…data), and by 1 CAAU instrumented in British Columbia (Burger & Powell 1990), were to depths < 20 m; thus, I assumed that no dives by either CAAU or LEAU were deeper than 20 m. To estimate costs of diving, I used the modeling approach of Lovvorn et al (2004). This approach estimates mechanical work against drag, buoyancy, and inertia of the body and entrained water (added mass) during each swimming stroke at different depths, and then converts mechanical work into aerobic work (chemical substrate requirements) by means of an aerobic efficiency η (Lovvorn 2007). For a larger wing-propelled alcid (TBMU) it was previously shown that inertial work is a negligible fraction of the total mechanical work of diving compared to work against drag and buoyancy (Lovvorn et al 1999(Lovvorn et al , 2004.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…data), and by 1 CAAU instrumented in British Columbia (Burger & Powell 1990), were to depths < 20 m; thus, I assumed that no dives by either CAAU or LEAU were deeper than 20 m. To estimate costs of diving, I used the modeling approach of Lovvorn et al (2004). This approach estimates mechanical work against drag, buoyancy, and inertia of the body and entrained water (added mass) during each swimming stroke at different depths, and then converts mechanical work into aerobic work (chemical substrate requirements) by means of an aerobic efficiency η (Lovvorn 2007). For a larger wing-propelled alcid (TBMU) it was previously shown that inertial work is a negligible fraction of the total mechanical work of diving compared to work against drag and buoyancy (Lovvorn et al 1999(Lovvorn et al , 2004.…”
Section: Methodsmentioning
confidence: 99%
“…Values of η depend strongly on the accuracy of the mechanical model (i.e. η is specific to a given model), and subsume thermoregulation costs (Lovvorn 2007). Depending on body size, water temperature, and exercise level, heat generated by exercising muscles may be less than heat lost, or may completely replace heat lost so that no shivering thermogenesis is needed.…”
Section: Thermoregulation and Aerobic Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…One response to that difficulty has been the development of bioenergetics modelling. The contribution by Lovvorn (2007) illustrates this type of approach in understanding thermoregulation in diving animals. However, Lovvorn also raises the point that it remains very difficult to reconcile the time-scales at which the various subcomponents involved in preserving heat balance proceed, i.e.…”
Section: This Volumementioning
confidence: 99%